A Seven-Year retrospective review of stroke admissions in Benin-City, Southern Nigeria - Edith Kayode-Iyasere; Francis Odiase (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2019)
Background: Stroke is a significant cause of hospital admissions, disability and mortality, but there is a lack of information on stroke in parts of the southern region of Nigeria. Objective: To analyze the frequency of stroke admissions, clinical presentations, risk factors, stroke types and outcomes over seven years, in a secondary level hospital in southern Nigeria. Methods: This was a retrospective study. The hospital record of patients hospitalized between January 2006 and December 2012 at the Central Hospital, Benin-City with the diagnosis of stroke based on the World Health Organization (WHO)-clinical criteria, were studied. Results: Four hundred and nineteen patients with stroke were hospitalized during the study period; this accounted for 3.1% of all the medical admissions. The mean age was 62.4 ± 13.6 years. There were 222 (53%) males and 197(47.0%) females. Ischaemic stroke occurred among 71% of cases; others included intra-cerebral haemorrhage (26%) and subarachnoid haemorrhage (3.1%). The main presenting features included hemiparesis (69%) and sudden loss of consciousness (27.2%). The risk factors included hypertension (84%) and diabetes mellitus (12.2%). The 7, 14 and 30 days case fatality rates were 21.2%, 25.5% and 30.8% respectively. A higher case fatality rate was recorded in haemorrhagic stroke compared to ischaemic stroke (68.8% vs 24%, p = 0.0001). Conclusion: Stroke was a significant cause of mortality amongst medical admissions and hypertension was the most common risk factor. Closer attention to the risk factors for stroke may likely help to reduce the burden of stroke.